The Influence of Innovation Attributes and Level of Trust on Mobile Banking Adoption - Dian Purwati, E; Soewarno, N; ., Isnalita (KnE Social Sciences, 2018)
The rapid progress and development of information technology has affected the banking industry. The main priority of the Bank is not only about banking but also about services supported by large investments in the field of Information Technology. And Mobile banking is one manifestation of the progress of these technological developments. This research is about two points, first point is attribute innovation that customers need to adopt mobile banking and the second points is trust factors desired by customers from mobile banking providers in order to adopt the service. This research also study about how these two things affect the attitude of the customer and the value of customer to adopt mobile banking. So that research can be a reference for mobile banking provider to develop their services for customer. Because there are various advances in technology that exists today, customer desired not only easy of use but also compatibility Because some telecommunication companies and online sales agencies offer similar functionality to mobile banking. proven in this research is what consumers wanted by the customer is the relative advantage that can be offered by the bank and also the integrity confidence of the bank itself against customer. Thus it is expected that banks can continue to innovate to provide the best service desired by customers, by developing the field of information technology